Deterministic Inventory Routing Problem (DIRP): a literature review - Harahap, Afif Zuhri Muhammad Khodri; Abdul Rahim, Mohd Kamarul Irwan (ExcelingTech Publishers, 2017)
Vendor managed inventory (VMI) is a management policy in which the supplier implements the responsibility of maintaining the inventory at the retailers to confirm that they will not run out of stock. Under the VMI policy, the supplier takes responsibility for managing the retailers. Moreover, delivery times to the retailers are no longer set by responding to retailers' orders, instead the supplier establishes when each delivery takes place. Therefore, this study reviewed the main publications on single item (vehicle) related to deterministic inventory routing problem (DIRP). Under this approach, the order delivery is in congruence with deterministic demand rates. The objective of DIRP is to resolve a flow strategy that can minimise operational and inventory holding costs without having a stock-out according to a retailer planned schedule.In this study, the focus in on the single-warehouse, multipleretailer vendor managed inventory (SWMR-VMI), where all retailers face a deterministic and constant demand rate.